A semantic prosody analysis of the lexical halal - Norsimah Mat Awal,; Hishamudin Isam, (Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
Language analysis in real world linguistic is a method in observing language usage phenomena that is mobilized by a process or the social practice of a society. The usage phenomenon is represented by lexical (word) choice of language users in a society. This is because every lexical item of a language would be based on meaning and values that would capture and highlight the cultural expressions of a nation. Based on this premise, this study aims to specifically discuss the cultural expressions identified from the investigation on the lexical item halal that is often used by society in discussing matters pertaining to everyday life. This analysis utilizes the cognitive linguistics perspective in explaining the usage of the lexical halal that can be visualized in schematic representation form. Aided by the display of concordance and wordlist from the Antcom program, this study discovered that the lexical halal is used in a variety of domains and is not restricted to food only. In addition, the lexical halal is also able to explain issues pertaining to livelihood, wealth, items/objects and issues that touch on status.